Automated Bricklaying Robot (ABR-1) / Syaima Mohd Fauzi and Ezzat Fahmi Ahmad - Mohd Fauzi, Syaima; Ahmad, Ezzat Fahmi (2023)
In Malaysia, the conventional method is still widely used, though the Industrialised Building System (IBS) has been successfully adopted in the government sector. Malaysia’s construction industry needs more workers as conventional methods are widely used. Right now, the Malaysian construction industry widely uses the convention method, in which skilled workers are needed to construct, and a lack of skilled workers led to the innovation of the automated bricklaying robot. Therefore, the objective of this research is to identify the current issues and problems of bricklayers, to assemble the simulation by improvising the design of bricklaying productivity and to demonstrate an entrepreneurial skill in proposing bricklaying productivity which can be marketable. Finding the current problems, suggesting and building a new machine, and assessing the marketability of the product were done in order to improve and remedy every flaw in the current bricklaying robot and technology. This research is based on a secondary data review (i.e., past data source by government publications, websites, books, journal article, internal records etc.) (Wagh, n.d.) and observation at the construction site to see the situation of bricklayers and also includes a SketchUp mockup of the machine. ABR-1, an automated bricklaying robot, is suggested as a solution to the problems of a shortage of skilled labourers, delays, and costs.